Democracy Aid and Electoral Accountability. (January 2019) - Heinrich, Tobias; Loftis, Matt W.
Although foreign policies often fail to successfully promote democracy, over a decade of empirical research indicates that foreign aid specifically for democracy promotion is remarkably successful at improving the survival and institutional strength of fragile democracies. However, these measures cannot tell us how well democracy aid supports the central promise of democracy: accountable government. Since institutions can be subverted in various ways that undermine accountability, it is vital to know whether democracy aid supports accountability to assess its overall success. We provide evidence for this by analyzing incumbent turnover in elections, following poor economic performance—the economic vote—as a measure of voting to achieve performance accountability. In our analysis of over 1, 100 elections in 114 developing countries between 1975 and 2010, we find distinct evidence that increasing receipt of democracy aid is associated with more economic voting. Results are robust to numerous alternative empirical specifications.